Cu nanowires paper interlinked with cobalt oxide films for enhanced sensing and energy storage. Issue 61 (11th July 2019) - Yuan, Ruimei; Li, Hejun; Yin, Xuemin; Wang, Peipei; Lu, Jinhua; Zhang, Leilei
Abstract : A Cu-NWs paper is synthesized by a one-step method, which supports to deliver good performance for the catalytic oxidation of glucose and energy storage. Abstract : A Cu-NWs paper synthesized by a one-step method is first presented. Owing to its good conductivity, it is an effective framework to interlink TMOs and prevent aggregation. For a practical application, the core–shell Cu NWs@ultrathin CoO x delivers good performance for the catalytic oxidation of glucose and energy storage, with a sensitivity of 396.57 μA mM −1 cm −2 and a capacitance of 797.7 F g −1 (1 A g −1 ).